2015
DOI: 10.1002/cbf.3114
|View full text |Cite
|
Sign up to set email alerts
|

Bag‐1 promotes cell survival through c‐Myc‐mediated ODC upregulation that is not preferred under apoptotic stimuli in MCF‐7 cells

Abstract: Bag-1, Bcl-2 associated athanogene-1, is a multifunctional protein that can regulate a wide variety of cellular processes: proliferation, cell survival, transcription, apoptosis and motility. Bag-1 interacts with various targets in the modulation of these pathways; yet molecular details of Bag-1's involvement in each cellular event are still unclear. We first showed that forced Bag-1 expression promotes cell survival and prevents drug-induced apoptosis in MCF-7 breast cancer cells. Increased mRNA expressions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Despite these differences, Bag-1 overexpression was a common feature in all breast cancer subtypes. In accordance with this finding, ectopic expression of Bag-1 increased proliferation, whereas its silencing increased apoptotic cell death in all cell lines tested independent of their receptor and tumorigenicity status [7, 31–33].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Despite these differences, Bag-1 overexpression was a common feature in all breast cancer subtypes. In accordance with this finding, ectopic expression of Bag-1 increased proliferation, whereas its silencing increased apoptotic cell death in all cell lines tested independent of their receptor and tumorigenicity status [7, 31–33].…”
Section: Discussionsupporting
confidence: 71%
“…Through these interactions, Bag-1 is involved in the regulation of diverse cellular processes such as apoptosis, proteostasis, transcription and motility [5]. Bag-1 protects cells from a variety of apoptotic signals [2, 6], and plays important roles in breast cancer development and chemoresistance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the MYC signalling pathway is seen as one of the major drivers in dysregulated polyamine metabolism-associated cancers. As members of the MYC family are frequently amplified or overexpressed in cancer, the regulation of polyamine biosynthesis by MYC family genes plays a substantial role in multiple cancer types including leukaemias and lung, neural and breast cancers 3337 . Furthermore, the link between MYC, hypusine formation and eIF5A activation likely plays a role in neoplastic transformation 9 (FIG.…”
Section: Polyamines and Cancermentioning
confidence: 99%
“… 75 This MYC-mediated regulation of polyamine biosynthesis has been confirmed in multiple cancers, such as leukemias, lung carcinomas, neuroblastomas, and breast cancers. 76 79 Recent studies revealed that mTORC1 stabilizes pro-S-adenosyl methionine (AdoMet) decarboxylase (pro-AdoMetDC), leading to increased AdoMetDC to further promote polyamine biosynthesis in prostate cancer. MYC has been linked to mTORC1 activation by increasing nutrient import.…”
Section: Myc Regulation Of Polyamine Biosynthesismentioning
confidence: 99%